Cytogenetics of the genus Musa - Sheperd, K.; International Network for the Improvement of Banana and Plantain (1999)
This book provides important information resulting from a lifetime dedicated to banana research. Ken Shepherd has not only devoted his life to studying bananas, but has focused on an area much neglected by other researchers, Musa cytology. The publishing of this book is especially timely given the recent upsurge in interest in Musa karyology and the new methods that are now available for studying Musa chromosomes.